THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL INTENTIONS IN GENERATION Z MUSLIM - Timur, Yan Putra; Herianingrum, Sri (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: This study aims to examine the effect of entrepreneurship education based on the business history of the Prophet Muhammad on the intentions, motivation and knowledge of generation Z Muslims to become entrepreneurs. Methods: The research approach used in this research is quantitative, using the PLS-SEM method as the evaluation model. Questionnaires were given to 100 respondents from East Java with Generation Z criteria and were Muslim. Results: The results show that entrepreneurship education based on the business history of the Prophet Muhammad has a positive influence on the intentions and motivation of generation Z Muslims to become entrepreneurs. Likewise, entrepreneurial knowledge has a positive influence on the intentions and motivation of Generation Z Muslims for entrepreneurship and entrepreneurial motivation variables do not positively influence intentions to become entrepreneurs. Conclusion and suggestion: These results indicate that entrepreneurship education based on the business history of the Prophet Muhammad has very significant potential in efforts to increase the number of entrepreneurs in Indonesia through increasing intention and motivation. The delivery of material can also use digital media and invite endorsers such as scholars or entrepreneurs related to Muslim entrepreneurs who apply Islamic values "‹"‹in their business and are widely known by Generation Z.